TRUMP AND AMERICAN PRESIDENCY (British Journal of Global Ecology and Sustainable Development, 2023)
This scientific article examines the presidency of Donald J. Trump and its impact on American politics and society. Trump's unconventional campaign and tumultuous term in office were marked by controversy, polarization, and a populist message that resonated with many Americans. His presidency highlighted the deep divisions in American society and raised questions about the role of social media and the media environment in American politics.